Targeting extracellular Hsp90: A unique frontier against cancer - Sager, Rebecca A.; Khan, Farzana; Toneatto, Lorenzo; Votra, SarahBeth D.; Backe, Sarah J.; Woodford, Mark R.; Mollapour, Mehdi; Bourboulia, Dimitra (Frontiers in Molecular Biosciences, 2022)
The molecular chaperone Heat Shock Protein-90 (Hsp90) is known to interact with over 300 client proteins as well as regulatory factors (eg. nucleotide and proteins) that facilitate execution of its role as a chaperone and, ultimately, client protein activation. Hsp90 associates transiently with these molecular modulators during an eventful chaperone cycle, resulting in acquisition of flexible structural conformations, perfectly customized to the needs of each one of its client proteins. Due to the plethora and diverse nature of proteins it supports, the Hsp90 chaperone machinery is critical for normal cellular function particularly in response to stress. In diseases such as cancer, the Hsp90 chaperone machinery is hijacked for processes which encompass many of the hallmarks of cancer, including cell growth, survival, immune response evasion, migration, invasion, and angiogenesis. Elevated levels of extracellular Hsp90 (eHsp90) enhance tumorigenesis and the potential for metastasis. eHsp90 has been considered one of the new targets in the development of anti-cancer drugs as there are various stages of cancer progression where eHsp90 function could be targeted. Our limited understanding of the regulation of the eHsp90 chaperone machinery is a major drawback for designing successful Hsp90-targeted therapies, and more research is still warranted.